2016
DOI: 10.1038/srep22218
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and liver-specific alterations in lipid and acylcarnitine metabolism after a single bout of exercise in mice

Abstract: Intracellular lipid pools are highly dynamic and tissue-specific. Physical exercise is a strong physiologic modulator of lipid metabolism, but most studies focus on changes induced by long-term training. To assess the acute effects of endurance exercise, mice were subjected to one hour of treadmill running, and 13C16-palmitate was applied to trace fatty acid incorporation in soleus and gastrocnemius muscle and liver. The amounts of carnitine, FFA, lysophospholipids and diacylglycerol and the post-exercise incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
4
13
0
Order By: Relevance
“…However, in the studies that have suggested increased AC levels as a marker of insulin resistance, type 2 diabetes and cardiovascular diseases, the measurements were performed only in plasma or serum, and data regarding the AC content in tissues are lacking. To date, only a few studies have investigated the relationship between plasma and tissue AC contents 15 17 , 23 , 25 , 26 . Measurements of ACs in fed and fasted states showed that the plasma long-chain AC concentration reflects the AC content in cardiac tissue, but the data regarding the content in muscles are controversial 15 17 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…However, in the studies that have suggested increased AC levels as a marker of insulin resistance, type 2 diabetes and cardiovascular diseases, the measurements were performed only in plasma or serum, and data regarding the AC content in tissues are lacking. To date, only a few studies have investigated the relationship between plasma and tissue AC contents 15 17 , 23 , 25 , 26 . Measurements of ACs in fed and fasted states showed that the plasma long-chain AC concentration reflects the AC content in cardiac tissue, but the data regarding the content in muscles are controversial 15 17 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…From the observation of metabolite intermediates of glycolysis and the TCA cycle such as lactate being upregulated, we feel we can confidently state that known mechanisms of high intensity training were taking place in our cohort [ 26 ]. From the dysregulation of energy processes in the metabolomics data and the variation in carnitine species observed just above the significance cutoff, it is possible that these species were in fact perturbed in our system as has been noted by others ( Supplemental Table S2 ) [ 52 , 69 ]. A variety of factors may preclude this annotation, including age-based impairment of the acyl carnitine pathway that diminishes FA oxidation and study-to-study variation from different exercise training regimes [ 54 , 70 ].…”
Section: Resultsmentioning
confidence: 82%
“…The previous targeted metabolomic study for both the ETT and PMI cohorts provided great insight into statistically significant polar metabolites [ 26 , 27 , 45 ], but overlooked important nonpolar molecules changing due to each event. The recent annotation of lipids in both CVD and exercise has elucidated the critical roles these molecules serve in each event [ 24 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Therefore, the inclusion of lipidomic and multi-omic assessments in this manuscript provides a more in-depth profile of ETT and PMI molecular mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to skeletal muscle, the liver shows both an acute stress response to physical exercise [ 20 , 21 ] and long-term adaptations to this metabolic challenge. We have previously reported that exercise acutely upregulates genes involved in the immune response and glucose and fatty acid metabolism [ 20 ], such as peroxisome proliferative activated receptor gamma coactivator 1 alpha (Ppargc1a), pyruvate dehydrogenase kinase 4 (Pdk4), insulin receptor substrate 2 (Irs2), angiopoietin like 4 (Angptl4) and the carnitine transporter solute carrier family 22 member 5 (Slc22a5), whereas it downregulates fatty acid synthase (Fasn) [ 22 , 23 ]. By increasing mitochondrial fatty acid oxidation and suppressing lipid anabolic processes in the liver, training reduces hepatic fat content and improves NAFLD, even in the absence of weight loss [ 3 , 23 ].…”
Section: Introductionmentioning
confidence: 99%